A Concept of the Effective Surface Profile to Predict the Roughness Parameters of Worn Surface - Kovalev, Alexander; Yazhao, Zhang; Hui, Cao; Meng, Yonggang (Frontiers in Mechanical Engineering, 2019)
A new concept of the effective surface profile is proposed to facilitate the prediction of the wear texture on a surface under linear sliding conditions. The effective surface profile is a 2D phenomenological height characteristic that consist of the asperities of surface superimposed on a plane perpendicular both to the mean surface plane and to the direction of sliding. We hope to present a clear and compelling argument favoring the use of the effective surface profile as a versatile tool for characterization of rough surface subjected to an abrasive wear, calculation of contact characteristic at the sliding friction and for prediction of evolution of roughness parameters from virgin to the worn surfaces that being formed due to the mechanical wear. The effective surface profile can be successfully applied as for investigations of sliding abrasive wear under dry or lubricated conditions.